Tuning the electronic structure and SMSI by integrating trimetallic sites with defective ceria for the CO 2 reduction reaction - Charvi Singhvi; Gunjan Sharma; Rishi Verma; Vinod K. Paidi; Pieter Glatzel; Paul Paciok; Vashishtha B. Patel; Ojus Mohan; Vivek Polshettiwar (Proceedings of the National Academy of Sciences, 2025)
Heterogeneous catalysts have emerged as a potential key for closing the carbon cycle by converting carbon dioxide (CO 2 ) into value-added chemicals. In this work, we report a highly active and stable ceria (CeO 2 )-based electronically tuned trimetallic catalyst for CO 2 to CO conversion. A unique distribution of electron density between the defective ceria support and the trimetallic nanoparticles (of Ni, Cu, Zn) was established by creating the strong metal support interaction (SMSI) between them. The catalyst showed CO productivity of 49,279 mmol g −1 h −1 at 650 °C. CO selectivity up to 99% and excellent stability (rate remained unchanged even after 100 h) stemmed from the synergistic interactions among Ni-Cu-Zn sites and their SMSI with the defective ceria support. High-energy-resolution fluorescence-detection X-ray absorption spectroscopy (HERFD-XAS) confirmed this SMSI, further corroborated by in situ electron energy loss spectroscopy (EELS) and density functional theory (DFT) simulations. The in situ studies (HERFD-XAS & EELS) indicated the key role of oxygen vacancies of defective CeO 2 during catalysis. The in situ transmission electron microscopy (TEM) imaging under catalytic conditions visualized the movement and growth of active trimetallic sites, which completely stopped once SMSI was established. In situ FTIR (supported by DFT) provided a molecular-level understanding of the formation of various reaction intermediates and their conversion into products, which followed a complex coupling of direct dissociation and redox pathway assisted by hydrogen, simultaneously on different active sites. Thus, sophisticated manipulation of electronic properties of trimetallic sites and defect dynamics significantly enhanced catalytic performance during CO 2 to CO conversion.